Islamic Entrepreneurship: Making Ice Cream for Student Yunior High School Khairu Ummah - Murdifin, Imaduddin; Masri, Rasyid (LAA MAISYIR : Jurnal Ekonomi Islam, 2023)
Economic growth can be measured from various sectors, one of which is UMKM. Becoming a UMKM manager should be done early by the community. Islamic Entrepreneurship training at the Khairu Ummah School is conducted to provide basic knowledge and motivation for students to start entrepreneurship from an early age. The description of a business that has the potential to be developed is also exemplified, namely the culinary ice cream business. This training uses the PAR (participatory action research) method in the form of community service activities (PKM). The participatory approach is that the Khairu Ummah school as a partner is directly involved in every activity carried out so that partners can better understand and be able to directly practice what has been trained. The evaluation results showed that there was an increase in the participants' knowledge and skills of around 80% regarding the need for entrepreneurship and Islamic ways of entrepreneurship, as well as how to make halal and thayyib ice cream. This certainly provides new knowledge to students about Islamic entrepreneurship procedures.